2014
DOI: 10.1111/acel.12247
|View full text |Cite
|
Sign up to set email alerts
|

SIRT 1‐mediated epigenetic downregulation of plasminogen activator inhibitor‐1 prevents vascular endothelial replicative senescence

Abstract: The inactivation of plasminogen activator inhibitor-1 (PAI-1) has been shown to exert beneficial effects in age-related vascular diseases. Limited information is available on the molecular mechanisms regarding the negatively regulated expression of PAI-1 in the vascular system. In this study, we observed an inverse correlation between SIRT1, a class III histone deacetylase, and PAI-1 expression in human atherosclerotic plaques and the aortas of old mice, suggesting that internal negative regulation exists betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 49 publications
1
58
0
Order By: Relevance
“…This observation suggests that the H4K16 deacetylase activity of SIRT1 may possibly activate these genes by reducing spurious transcript production. Additionally, the loss of SIRT1 in atherosclerotic plaque may de-repress pro-atherosclerotic genes in a H4K16 acetylation dependent manner as suggested for plasminogen activator inhibitor-1 29 . These latter concepts are important in that they highlight a key point.…”
Section: What Is Epigenetics?mentioning
confidence: 97%
“…This observation suggests that the H4K16 deacetylase activity of SIRT1 may possibly activate these genes by reducing spurious transcript production. Additionally, the loss of SIRT1 in atherosclerotic plaque may de-repress pro-atherosclerotic genes in a H4K16 acetylation dependent manner as suggested for plasminogen activator inhibitor-1 29 . These latter concepts are important in that they highlight a key point.…”
Section: What Is Epigenetics?mentioning
confidence: 97%
“…Another marker of endothelial senescence, PAI-1, is also inhibited by SIRT1 through an epigenetic regulatory mechanism involving the reduction of acetylated histone 4 Lys-16 (H4K16) on the PAI-1 promoter (106,189). Indeed, in senescent ECs and aortas of old mice, improved endothelial function and reduced arterial stiffness have been observed during SIRT1 overexpression that reverses the increased PAI-1 levels (189).…”
Section: Sirt1 In Cell Senescence and Aging Processesmentioning
confidence: 99%
“…It has been reported that mice overexpression of SIRT1 preserved the endothelium function comparing with that of WT littermates fed with high-fat diet and overexpression of SITR1 in ApoE -/- mice developed less atherosclerotic lesions compared with the ApoE -/- controls [61]. The mechanism of SIRT1 improving atherosclerosis may include dilating arteries [59], preserving function of endothelium [60] and preventing endothelial senescence [63], downregulating neointima formation [64] and vascular modeling [65], decreasing Lox-1-induced foam cell formation [62] and protecting against DNA damage [66]. It has been reported that H 2 S upregulated SIRT1 to exert some of its protective effects.…”
Section: H2s Epigenetic Regulation Atherosclerosis Is An Important Famentioning
confidence: 99%